Identification of Medicinal Plants in The Area of KPPH Farmer at Talang Mulya on Wan Abdul Rachman Great Forest Park - Mayangsari, Ayu; Indriyanto, Indriyanto; Bintoro, Afif; Surnayanti, Surnayanti (Jurnal Sylva Lestari, 2019)
Forests are a source of various types of medicinal plants. Plants that live wildly in forest areas are also included in the Forest Park area, Wan Abdul Rachman. Type identification is the first step for the use and preservation of these medicinal plants. Therefore a study was conducted which aims to determine the types, density of each population and the degree of dominance of each population of medicinal plants. This research was carried out in the farmer's group cultivated area of Kelompok Pengelola dan Pelestari Hutan (KPPH) Talang Mulya Tahura Wan Abdul Rachman. This research was conducted using a double plot method. The number of sample plots is 87 plots, each measuring 2m x 2m. The variables observed included plant species, the density of each population and the degree of dominance of each population of medicinal plants. The results of this study were identified 29 types of medicinal plants belonging to 18 plant families. The majority of medicinal plants are dominated by awar-awar, while the lowest is the curcuma and pepper. There are quite a lot of medicinal plants in the area cultivated by KPPH Talang Mulya farmers, but there are medicinal plants which are threatened by populations such as temulawak, allegedly because they are used by the community without cultivation. Keyword: forest, forest park, medical plants.